Resected tumours of the sublingual gland: 15 years' experience. Issue 6 (July 2016) - Huang, Tung-Tsun; Chou, Yu-Fu; Wen, Yu-Hsuan; Chen, Peir-Rong
Abstract: Sublingual gland tumours are rare, and we have evaluated the clinical features and prognosis of patients treated at a tertiary medical centre in eastern Taiwan. We retrospectively reviewed the cases of nine patients with sublingual gland tumours that were resected from December 1993 to November 2008, four of whom were men and five women. The median (range) age at diagnosis was 52 (39-63) years. Seven had malignant tumours, of which adenoid cystic carcinoma was the most common. All patients with malignant tumours had neck dissections, and four had cervical lymph node metastases. The incidence of lymph node metastases was much higher in patients with advanced primary tumours (T1/2 compared with T3/4: one out of three compared with three out of four). All patients with malignant tumours were given adjuvant radiotherapy. There were no local failures. One patient had regional recurrence in the neck and had a successful further resection. Three patients developed distant metastases, and two died during the follow-up period. Our results suggest that radical resection with postoperative radiotherapy offers adequate local and regional control for malignant sublingual gland tumours. Neck dissection is beneficial, especially for T3/4 disease.